THE CORRELATION BETWEEN STUDENTS’ MASTERY ON LEXICAL COLLOCATION AND THEIR READING COMPREHENSION - Wulan Trisviana; Rudi Afriazi; Gita Mutiara Hati (Journal of English Education and Teaching, 2019)
The aims of this research were to find out the correlation between students’ mastery of lexical collocation and their reading comprehension. This research applied correlational study which used quantitative design. The subjects were 66 of the Fifth-Semester Students of English Education Study Program at University of Bengkulu in Academic Year 2018/2019. The data were collected from two instruments: (1) lexical collocation test was used to get data about students’ mastery of lexical collocation and (2) reading comprehension test was used to get data about students’ reading comprehension achievement. The result of the two instruments counted by using Pearson’s Product Moment formula and checked it by using SPSS 22 Program. The conclusion were (1) The result score of lexical collocation test showed that 53% of the students got score over 70, it means that half of the total subject of the students have a good knowledge of collocation especially in lexical collocation. (2) There was high significant correlation between students’ mastery of lexical collocation and their reading comprehension. The result of calculation using Pearson Product moment formula and SPSS 22 Program can be seen in table 4.1 which showed the score of arithmetic r > the score of r table (0,825 > 0,315). It means that Ha was accepted and H0 was rejected.